Molecular genetic investigations of autism. - Maestrini, E; Marlow, A; Weeks, D; Monaco, A (1998)
Genetic factors are likely to play a major role in the etiology of autism. The genetics of the disorder is however complex, probably involving the action of several genes. In an attempt to identify autism susceptibility loci we are currently undertaking a systematic screening of the whole human genome using multiplex families. We describe the resources and the methods needed to achieve such a task, including extensive collection of family data, semiautomated genotyping technology, and specialized statistical approaches for linkage analysis of complex traits.